Eksplorasi Metafora Keburukan Israel Berdasarkan Hosea 7 Sebagai Retrospeksi Spiritualitas Umat - Anon Dwi Saputro (Predica Verbum: Jurnal Teologi dan Misi, 2023)
This article explores the metaphor of Israel's ugliness in Hosea 7 as a retrospective of the people's spirituality. This research is motivated by the need for more research that comprehensively discusses the metaphors of Hosea 7. Some studies only discuss one or two metaphors from the four metaphors described by Hosea 7. The method used is thematic analysis modeling. In the study, the author will pay attention to the interconnectedness of the text in the context of Hosea 7 and the book of Hosea as a whole through the lens of metaphor. The study found that the metaphor refers to the wickedness and sin committed by Israel. It is related to adultery and power; her identity has become blurred and contaminated with other nations; they joined the nations to gather strength rather than relying on God and have worshipped idols. The exploration of metaphors in Hosea 7 is a retrospective study of people's spirituality. Learning from Israel's ugliness enables retrospection so as not to repeat the same mistakes and make the people more attached to God.